2000
DOI: 10.1152/ajpheart.2000.279.3.h1397
|View full text |Cite
|
Sign up to set email alerts
|

Selective transport of adenosine into porcine coronary smooth muscle

Abstract: Adenosine (ADO), an endogenous regulator of coronary vascular tone, enhances vasorelaxation in the presence of nucleoside transport inhibitors such as dipyridamole. We tested the hypothesis that coronary smooth muscle (CSM) contains a high-affinity transporter for ADO. ADO-mediated relaxation of isolated large and small porcine coronary artery rings was enhanced 12-fold and 3.4-fold, respectively, by the transport inhibitor, S-(4-nitrobenzyl)-6-thioinosine (NBTI). Enhanced relaxation was independent of endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 44 publications
(64 reference statements)
5
18
0
Order By: Relevance
“…In a recent study, increased relaxation to exogenously applied Ado was observed during Ado transporter inhibition with NBTI in porcine coronary arteries. 12 This finding supports the idea of an intracellular action of Ado in regulating arterial tone.…”
Section: Lai Et Alsupporting
confidence: 79%
See 1 more Smart Citation
“…In a recent study, increased relaxation to exogenously applied Ado was observed during Ado transporter inhibition with NBTI in porcine coronary arteries. 12 This finding supports the idea of an intracellular action of Ado in regulating arterial tone.…”
Section: Lai Et Alsupporting
confidence: 79%
“…10,11 Recent investigations suggest an intracellular, vascular tone-enhancing action of Ado in smooth muscle cells. 12 In the present study, we therefore investigated a possible receptor independent effect of Ado on the desensitization of Ang II-induced contractions in the renal microvasculature. We show that Ado completely restores the response of isolated, perfused afferent arterioles on repeated applications of Ang II in mice.…”
mentioning
confidence: 99%
“…Second, ADO may alter P s RSA via binding to ADO receptors and use of a nonreceptor-mediated pathway such as an ADO transporter. It has been shown that ADO transporters can take ADO up from smooth muscle intracellular space with a K m of 17.6 Ϯ 2.6 ϫ 10 Ϫ6 M and a V max of 5.1 Ϯ 0.5 ϫ 10 Ϫ12 mol⅐min Ϫ1 ⅐mg wet tissue Ϫ1 in intact porcine coronary artery rings (44). It is possible that the transported intracellular ADO is converted to AMP, which can activate AMP-activated protein kinase (AMPK), resulting in AMPK-increased nitric oxide (NO) synthesis by stimulation of endothelial NO synthase (eNOS) activity (37).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, microdialysates were diluted 10-fold with water containing 10 nmol/L [U 13 C 10 -U- 15 N 5 ] adenosine as an internal standard. HPLC separations were performed using a 5-m C18 column using pentadecafluorooctanoic acid as an ion-pairing reagent.…”
Section: Methodsmentioning
confidence: 99%
“…11 Dipyridamole is an inhibitor of this nucleoside transporter and is proposed to act by blocking adenosine uptake, thus increasing plasma and interstitial levels of adenosine 12 and potentiating adenosine actions in humans. 13 High-affinity nucleoside transporters are expressed in endothelial 14 and vascular smooth muscle cells 15 and may provide a barrier to intravascular adenosine reaching myocardial cells. Indeed, animal studies suggest that most of the adenosine infused into the arterial circulation might be trapped by the endothelium.…”
mentioning
confidence: 99%